Resurgent Africa : structural transformation in sustainable development - Oyelaran-Oyeyinka, Banji, 1955- (Anthem studies in peace, conflict and development., 2020)
'Resurgent Africa: Structural Transformation in Sustainable Development' is a study of structural change dynamics in Africa and its effect on job creation, living standards and the efficiency of productive cities through manufacturing productivity growth that benefit the majority. Empirical data from selected African countries, including Nigeria, Ghana, South Africa, Kenya, Rwanda and Ethiopia, provides in-depth analysis and knowledge of the continent's diversified economies by establishing relationships between industrialization trends; rates of urbanization; and urban living standards, income growth and employment in Africa. The findings reveal unconventional pathways of structural change, patterns of jobless growth suggesting economic growth that does not necessarily lead to employment, dominance of services at the expense of manufacturing industry explaining the regress in Africa's industrial sector and occurrence of structural transformation without improvement in labour productivity. These are important concerns for Africa's long-term development leading to the conclusion that sustainable urbanization and industrialization are not only closely connected but also key drivers of economic change. The book includes recommendations for policymakers to adopt a new approach to development for a resurgent Africa.